Phenotypic and Genotypic Antibiotic Resistance of Staphylococcus warneri and Staphylococcus pasteuri Isolated from Stuffed Mussels - Nermin Berik; Dilek Kahraman Yılmaz (Aquatic Sciences and Engineering, 2024)
This study aimed to assess the presence of Staphylococcus species in stuffed mussel samples sold in Çanakkale province and to determine the antibiotic resistance of the isolates. A total of 246 stuffed mussel samples were examined, and two different Staphylococcus (S. warneri and S. pasteuri) were isolated from 12.19% of the samples. Among the Staphylococcus isolates, S. warneri was detected at a rate of 73.33% and S. pasteuri at 26.67%. Bacterial isolates (N=30) were examined for their resistance to amoxicillin/clavulanic acid (30 µg), ampicillin (10 μg), erythromycin (15 µg), clindamycin (10 µg), vancomycin (30 µg), oxacillin (5 µg), tetracycline (30 µg), doxycycline hydrochloride (30 µg), chloramphenicol (30 µg), streptomycin (10 µg), gentamicin (10 µg), kanamycin (30 µg), nalidixic acid (30 µg), ciprofloxacin (5 µg), meropenem (10 µg), imipenem (10 µg), sulfamethox/ trimethoprim (25 µg), cefotaxime (30 µg), cephalothin (30 µg), ceftriaxone (30 µg), and levofloxacin (5 µg) antibiotics. Resistance to amoxicillin/clavulanic acid and erythromycin was found in all S. warneri isolates. In addition, all S. pasteuri isolates were found to be resistant to amoxicillin/ clavulanic acid. In S. warneri isolates, at least three resistance genes (BlaTEM, tetB-6, tetK-8) and up to eight resistance genes (BlaTEM, tetB-6, tetK-8, strA-strB, aphAI-IAB, ermC) were identified. All S. pasteuri isolates exhibited blaTEM, strA-strB, and aphAI-IAB resistance genes. In conclusion, it was determined that antibiotic-resistant S. warneri and/or S. pasteuri contaminates stuffed mussel samples. This study will serve as a valuable resource for enhancing monitoring strategies in stuffed mussel production. Further studies should be conducted to determine whether the products are suitable for food safety. Therefore, it is necessary to clarify the disease effects and mechanisms of the pathogens identified in stuffed mussels.